Development of novel paracetamol/naproxen co-crystals with an improvement in naproxen solubility. - Amal Fakhrulddin Al-Dulaimi; Myasar Mohammed Al-Kotaji; Faris Thanoon Abachi (College of Pharmacy University of Baghdad, 2022)
Co-crystals are new solid forms of drugs that could resolve more than one problem associated with drugs formulations like solubility, stability, bioavailability, mechanical and tableting properties. A preliminary theoretical study for estimating the possible bonding between the co-crystal components (paracetamol and naproxen) was performed using the ChemOffice program. The results revealed a high possibility for bonding between paracetamol and naproxen and indicated the ability of molecular mechanics study to predict the co-crystal design.        In this work, four different methods were used for the preparation of three different ratios 1:1, 2:1, and 1:2 of paracetamol:naproxen co-crystals. The four methods are liquid-assisted grinding, solvent evaporation method, ultrasonic-assisted co-crystallization, and microwave-assisted co-crystallization. The characterization of the prepared co-crystal was performed by Fourier transform infrared spectroscopy, Thermogravimetric Analysis, Differential scanning calorimetry, Powder X-Ray diffraction, and Field emission scanning electron microscopy.        The results showed that the most successful method for co-crystal production was solvent evaporation methods. The FTIR and DSC results indicated the formation of paracetamol-naproxen co-crystals when prepared by using the solvent evaporation method in the three ratios 1:1 (N1), 2:1 (N2), and 1:2 (N3). Moreover, the PXRD results confirm the previous conclusions.        A solubility study was conducted to compare the water solubility of pure paracetamol and naproxen with co-crystals solubility. The naproxen solubility was improved by more than two times in (1:1) and (1:2) paracetamol/naproxen co-crystals.        To conclude, this work succeeded in formation of new paracetamol/naproxen co-crystals, which can be considered as a new promising technique for formulation of these two drugs with an obvious enhancement in naproxen solubility and crystallinity. This could be exploited in preparation of tablets with possible enhancement in dissolution and bioavailability, however, further work is needed to prove this assumption.